Effects of a training program to enhance autonomy supportive behaviors among youth soccer coaches - Langdon, J.; Schlote, R.; Harris, B.; Burdette, G.; Rothberger, S. (Journal of Human Sport & Exercise, 2015)
This study aimed to evaluate the prevalence and implementation of a training emphasizing the use of autonomy supportive coaching behaviors among youth soccer coaches in game-play situations as well as evaluating its effects on motivational processes among athletes. Participants included youth sport soccer coaches and their intact teams. Coaches received a series of autonomy-supportive coaching training interventions based on successful programs in general and physical education (Reeve, Jang, Carrell, Jeon, & Barch, 2004; Cheon, Reeve, & Moon, 2012). Athletes completed questionnaires to assess perceived autonomy support, basic need satisfaction, and motivation (Harris & Watson, 2011). Observations indicated coaches were not able to significantly modify their behaviors, yet reflectively reported modest implementation of autonomy supportive behaviors. Coaches believed the training influenced their coaching style/philosophy in regards to the coach-athlete relationship and communication styles, emphasizing choice and rationales. Continued research is needed to enhance use of autonomy supportive behaviors with volunteer coaches in a youth sport environment. See more at: http://www.jhse.ua.es/jhse/article/view/684#sthash.ODSEE1NB.dpuf